ANTIBACTERIAL POTENTIAL OF LIME (Citrus aurantifolia) ON THE GROWTH OF Streptococcus mutans (POTENSI ANTIBAKTERI JERUK NIPIS (Citrus aurantifolia) TERHADAP PERTUMBUHAN Streptococcus mutans) - Jeffrey (Fakultas Kedokteran Gigi Unjani, 2022)
Streptococci have a variety of solid virulence factors that allow various infections to occur. Streptococcus mutans is an obligate biofilm organism and is considered the primary etiology of dental caries. Lime (Citrus aurantifolia) is widely consumed because of its natural safety factors and is a vital ingredient in most herbal ingredients with antibacterial properties. Prevention in dentistry needs to be improved, one of which is through the potential of herbal plants to reduce world health problems, especially in Indonesia. Objective To determine the possibility of lime antibacterial compounds inhibiting the growth of Streptococcus mutans. Streptococcal groups, especially S. mutans, are aciduric and acidogenic organisms and can create environmental conditions that lethal to other bacteria. Streptococcus mutans produces several extracellular sucrose metabolite enzymes that contribute to the organism's ability to cause dental caries. Streptococcal virulence factors are usually due to adesin attachment to cell surface proteins, glucosyltransferase (GTF) production, acid production, and acid tolerance. Oranges are one of the largest plant species distributed throughout the world. Plants of the citrus genus are mainly valued for their edible fruit and traditional medicinal value and have an important role in health. Lime is a herbal plant that has the potential as an antibacterial against streptococci because it contains beneficial active compounds such as saponins, flavonoids, citric acid, amino acids, essential oils, resins, glycosides, vitamin B1, vitamin C, citric acid, fats, iron, calcium, sulfur, phosphorus, and is expected to be a choice of chemical drugs that have many side effects. Conclusion Lime is a herbal plant that contains antibacterial compounds that show various biological activities, are proteolytic and lipolytic, and contain active antibacterial compounds that are expected to reduce the incidence of dental and oral diseases. DOI : 10.54052/jhds.sd22.p185-194